Demonstrating RA-TDMAs+ for robust communication in WiFi mesh networks - Almeida, Diogo (2022)
This work will demonstrate a new flavor of the RA-TDMA set of protocols, namely RA-TDMAs+, which uses IEEE-802.11 (WiFi) COTS hardware in ad-hoc mode to set up a dynamic mesh network of mobile nodes with highbandwidth. The protocol uses topology tracking to configure the TDMA frame and robust relative synchronization to define the TDMA slots without resorting to a global clock and in the presence of interfering traffic. The demo will set up a small-scale testbed using COTS hardware, thus evidencing the feasibility of the approach, and it will show 1clive plots 1d of the temporal (synchronization) and topological views of the network.